El Salvador : Technical Assistance Report-The Capacity Development National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report, 2020)
A technical Assistance (TA) Mission was conducted by CAPTAC-DR1 from May 14 to 18, 2018 with the objective of supporting the Central Reserve Bank of El Salvador (CBR) in its efforts to strengthen its national accounts statistics for decision making. The TA mission covered the following topics: compilation of an Input-Output Table (IOT) for 2014; as well as to follow up on the recommendations made in previous TA missions to disseminate Supply and Use Tables (SUT) for 2015 and thereafter, as part of the national accounts' series with base year 2005. In addition, the mission provided training to the Department of National Accounts (DNA) team of the CBR in the methodological and conceptual aspects necessary for the analysis and application of the IOT as a statistical and analytical tool.